Factors Affecting Organizations Intention to Adopt Cloud Computing: A Study of Thai FinTech Enterprises - Suraratsamee , Rat; Luenam, Pramote; Ingsrisawang, Lily (Journal of Applied Statistics and Information Technology, 2023)
The purpose of this research was to study the factors that affect organizations’ intention to adopt cloud computing. The data were collected from a simple random sample of 256 staff who have experience with cloud computing and have worked in the FinTech industry. The data were analyzed through Structural Equation Model to evaluate the direct and indirect effects of various factors on the organizations’ intention to adopt cloud computing. According to analysis results, the relative advantage of cloud computing and the environment supporting conditions have a significant positive influence on the perceived usefulness and also have an indirect effect on the adoption intention through the perceived usefulness. However, organization readiness does not have a significant influence on the perceived usefulness and the perceived ease of use. In addition, the organization readiness does not have a significant indirect effect on the adoption intention. The results also show that the relative advantage of cloud computing and the environment supporting conditions have a significant positive influence on the perceived ease of use and they also have a significant indirect effect on the adoption intention through the perceived ease of use. The results of this study are beneficial for organizations that are planning to adopt cloud services and give guidance for implementing corporate governance practices, especially in the FinTech industry.